2007
DOI: 10.1007/s11199-007-9278-1
|View full text |Cite
|
Sign up to set email alerts
|

Video Game Characters and the Socialization of Gender Roles: Young People’s Perceptions Mirror Sexist Media Depictions

Abstract: Video game characters are icons in youth popular culture, but research on their role in gender socialization is rare. A content analysis of images of video game characters from top-selling American gaming magazines showed male characters (83%) are more likely than female characters (62%) to be portrayed as aggressive. Female characters are more likely than male characters to be portrayed as sexualized (60% versus 1%), scantily clad (39% versus 8%) and as showing a mix of sex and aggression (39 versus 1%). A su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
199
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(218 citation statements)
references
References 35 publications
7
199
0
2
Order By: Relevance
“…Accordingly, the alternative models tested and proposed in Ferguson and Donnellan (2017) could be misleading for readers, as they are not theoretically wellanchored and are distant from our original hypotheses. Indeed, our findings are entirely consistent and sustained by previous research in the field of media effects (see Dill et al 2008;Dill and Thill 2007;Fox et al 2013Fox et al , 2014.…”
Section: It Is Easy To Knock Down a Straw Personsupporting
confidence: 91%
See 2 more Smart Citations
“…Accordingly, the alternative models tested and proposed in Ferguson and Donnellan (2017) could be misleading for readers, as they are not theoretically wellanchored and are distant from our original hypotheses. Indeed, our findings are entirely consistent and sustained by previous research in the field of media effects (see Dill et al 2008;Dill and Thill 2007;Fox et al 2013Fox et al , 2014.…”
Section: It Is Easy To Knock Down a Straw Personsupporting
confidence: 91%
“…In addition, female characters tend to play minor roles. These games not only affect the way young women view themselves, they also encourage young men to look at women as sex objects (Dill and Thill 2007). Confirming these findings, another recent study (Lynch et al 2016) evaluated 571 playable female characters in video games released from 1989 to 2014 and concluded that despite an increase in games featuring playable female characters, games still depict female characters as sexualized and in more minor roles.…”
Section: Is Playing With Sexist Video Games Just Harmless Fun?mentioning
confidence: 87%
See 1 more Smart Citation
“…"All women who live in a culture where the female body is treated as an object to be evaluated Dill and Thill's paper shows that video games do have some effect on society and how we view gender roles: " (Dill 2007, manuscript in preparation) found a positive correlation between violent videogame playing and endorsement of rape myths, including the myths that women secretly want to be raped and even "deserve" to be raped. Furthermore, those who played more violent videogames also endorsed more traditional views of sex roles, such as the idea that men are more capable as leaders and professionals, while women deserve less freedom than men and are subservient to men (Dill 2007, manuscript in preparation).…”
Section: Representation/recognitionmentioning
confidence: 99%
“…Likewise Dill & Thill, (2007) analyzed video games and found that 83% male characters are shown aggressive and strong while 60% female were portrayed as sexual object. In most of the games they were exploited sexually and victimized by the male character.…”
Section: Literature Reviewmentioning
confidence: 99%